SYNERGY OF MARKETING TOOLS AND ACCOUNTING-TAX ADMINISTRATION OF BUSINESS PROCESSES ENSURING THE FINANCIAL STABILITY OF THE COMPANY - BOBROVNYK, Valentyna; SKOROBOGATA, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the synergy between marketing tool systems and the mechanisms of accounting and tax administration of business processes in the context of ensuring the financial stability and sustainable development of a company. The study emphasizes that in modern conditions, where competition and regulatory pressure are intensifying, the integration of marketing, accounting, and taxation is becoming a critical factor in achieving business transparency, strategic flexibility, and compliance. The research identifies key risks associated with the lack of such integration, including non-transparency of marketing costs, duplication and distortion of financial information, difficulties in justifying the economic feasibility of marketing operations, and increased exposure to tax disputes and financial sanctions. The proposed concept is based on the “goals–intentions–expectations” model, which establishes a logical framework for aligning marketing strategies with accounting policies and tax planning. This model enables the creation of a unified evidence base for both internal users — management, investors, auditors — and external stakeholders, including tax and regulatory authorities. It ensures the transparency of marketing expenditures, the reliability of their reflection in financial reporting, and the legitimacy of related business decisions. It is substantiated that the integration of marketing and accounting–tax systems not only enhances the controllability of financial flows and the analytical capabilities of management but also contributes to the formation of a favorable business reputation. Ultimately, this approach increases sales volumes and profitability, strengthens investment attractiveness, raises the market value of the enterprise, and provides long-term competitive advantages in a dynamic business environment.